FAKTOR PEMILIHAN PERUMAHAN DI DESA AIR SANTOK KECAMATAN PARIAMAN TIMUR KOTA PARIAMAN SEBAGAI TEMPAT TINGGAL - gebi permata sari; yurni suasti (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
ABSTRACT Humans are never free from all the problems associated with the place where humans hum in daily life. Choosing housing according to needs is not easy, especially in Desa Air Santok there are several housing complexes that are very attractive to consumers. Increasing population growth makes increasing housing needs. Air Santok Village is experiencing population growth every year, this is due to the presence of housing in the Air Santok Village. This type of research is quantitative research using a descriptive approach. Data collection techniques using questionnaires and field observations. The purpose of this study was to determine housing selection factors in Air Santok Village, Pariaman Timur District, Pariaman City as a place to live (case study of Resident II Villa Mutiara housing and Tata Bhakri IV housing). Housing selection factors are viewed from the main factors consisting of price, near the workplace and far from the potential threat of natural disasters while supporting factors are close to parents' homes, housing environment and environmental safety. The final results of the study in the form of the main factors in the selection of Resident Villa Mutiara II housing and Tata Bhakri IV housing are far from the potential for natural disaster threats. The supporting factor for the selection of Resident Mutiara Villa II housing is the housing environment, while Tata Bhakri IV housing is near the parents' house. Keywords: Analysis, research environment, housing selection factors.